INDONESIA’S COVID-19 NATIONAL ECONOMIC RECOVERY PROGRAM: GETTING THE ECONOMY BACK ON TRACK - Yudisatria, Aria (The Scientia Journal of Economics Issues, 2024)
Since early 2020, the Covid-19 pandemic has significantly impacted the global economy, including Indonesia. The Indonesian economy contracted by 2.1% in 2020, leading to rising unemployment and poverty rates. To address these challenges, the Indonesian government implemented the National Economic Recovery Program (Program Pemulihan Ekonomi Nasional – PEN), a comprehensive policy package consisting of both substantive and procedural policy tools. Substantive tools targeted supply-side and demand-side interventions, such as tax incentives, interest subsidies, and social safety net expansions. Meanwhile, procedural tools facilitated the implementation of these policies through regulatory adjustments, budget reallocations, and institutional coordination. The PEN program was successful in mitigating the economic contraction in the short term, although its long-term effectiveness remains to be seen. This study examines the policy tools utilized by the Indonesian government in restoring the economy and evaluates their suitability within the Indonesian context.